KARAKTERISASI REAKTOR PLASMA BERARUS NEGATIF DENGAN KONFIGURASI ELEKTRODA TITIK-BIDANG DAN PENERAPANNYA PADA KAIN POLYESTER RAJUT GREY - Hasan, Siti Nurjannah; Muhlisin, Zaenul; Triadyaksa, Pandji; Arianto, Fajar (BERKALA FISIKA, 2019)
Research on characterisations of plasma reactor with negative current of square-point electrode configuration and its application on grey polyester knit fabric has been carried out. The objectives of this reseach were obtaining characterisation of negative plasma reactor, either with or without sample of the polyester knit fabric, getting ion mobility value, gaining the characterisation of irradiated polyester knit fabric of grey, and obtaining SEM results indicating the morphological changes of the fabric. A Plasma-Electrode Point Plasma reactor which is connected to a high-voltage DC power plant was used in this study. The size of pointfield electrodes was 15 x 15 cm2 with a 1.6 cm needle. The size of the grey knit polyester fabric used was 10 x 10 cm2. Variations in distance between electrodes were 1.5 cm, 1.8 cm, 2.1 cm 2.4 cm, 2.7 cm, 3.0 cm, and 3.3 cm. The results have shown that if the voltage increases, then the current value increses. The voltage which is needed to produce a lower current values is that the presence of a polyester knit fabric of grey. The highest voltage and current values witout sample can be found at a distance of 3.3 cm with a current value of 2.5 mA at a voltage of 3.027 kV, compared with presence of a sample, a current value of 1.6 mA at a voltage of 3.445 kV. The greater distance of the electrode, the smaller ion of the mobility is achieved. Based on the results of the water drop test showed that the longer the irradiation of the cloth, the faster duration of absorption. This is indicated by a distance of 2.4 cm in the duration of 5 minutes obtained the absorption time of 2.15 seconds while in the duration of 35 minutes obtained 1.47 seconds. In the SEM test, it is used 2 cloths where the first cloth used as a control or not subjected to plasma that has little damage where as the second fabric is subjected to plasma treatment with the time of irradiation is about 20 minutes that have damage or peeling on the surface of polyester knit fabrics grey.Keywords: Plasma corona, multi-point field, ion mobility, polyester fabric, textile treatment, the meeting properties of fabric.